Aligning Teacher and Student Perceptions on the Implementation of the Merdeka Curriculum in English Language Teaching in Kayong Utara - Negara, Kartika Yoga Eka Pratiwi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study explores the perceptions of both English teachers and junior high school students regarding the implementation of the Merdeka Curriculum in Kayong Utara, a rural district in Indonesia. Utilizing a quantitative approach, data were collected through two Likert-scale questionnaires distributed to 21 teachers and 250 students across several schools. The instruments were designed around seven key indicators: clarity of instruction, teaching method effectiveness, learning engagement, relevance of materials, feedback and assessment, learning independence, and classroom atmosphere. Descriptive statistical analysis revealed generally positive perceptions from both groups, particularly in terms of instructional clarity and classroom climate. However, the findings also indicated several perception gaps. Teachers tended to underestimate the effectiveness of their teaching methods and feedback practices, while overestimating students’ autonomy and the relevance of materials. Correlational analysis showed moderate alignment between teacher and student responses, suggesting the need for greater feedback mechanisms and contextual alignment in teaching strategies. This study highlights the importance of professional development and support systems in ensuring the success of a flexible, student-centered curriculum in under-resourced regions.